Toll‐like receptor 7/8‐matured RNA‐transduced dendritic cells as post‐remission therapy in acute myeloid leukaemia: results of a phase I trial. Issue 3 (3rd March 2020) - Lichtenegger, Felix S; Schnorfeil, Frauke M; Rothe, Maurine; Deiser, Katrin; Altmann, Torben; Bücklein, Veit L; Köhnke, Thomas; Augsberger, Christian; Konstandin, Nikola P; Spiekermann, Karsten; Moosmann, Andreas; Boehm, Stephan; et al.
Abstract: Objectives: Innovative post‐remission therapies are needed to eliminate residual AML cells. DC vaccination is a promising strategy to induce anti‐leukaemic immune responses. Methods: We conducted a first‐in‐human phase I study using TLR7/8‐matured DCs transfected with RNA encoding the two AML‐associated antigens WT1 and PRAME as well as CMVpp65. AML patients in CR at high risk of relapse were vaccinated 10× over 26 weeks. Results: Despite heavy pretreatment, DCs of sufficient number and quality were generated from a single leukapheresis in 11/12 cases, and 10 patients were vaccinated. Administration was safe and resulted in local inflammatory responses with dense T‐cell infiltration. In peripheral blood, increased antigen‐specific CD8 + T cells were seen for WT1 (2/10), PRAME (4/10) and CMVpp65 (9/10). For CMVpp65, increased CD4 + T cells were detected in 4/7 patients, and an antibody response was induced in 3/7 initially seronegative patients. Median OS was not reached after 1057 days; median RFS was 1084 days. A positive correlation was observed between clinical benefit and younger age as well as mounting of antigen‐specific immune responses. Conclusions: Administration of TLR7/8‐matured DCs to AML patients in CR at high risk of relapse was feasible and safe and resulted in induction of antigen‐specific immune responses. Clinical benefit appeared to occur more likely in patients <65 and in patients mounting an immune response. Our observations need to be validated in a larger patient cohort. We hypothesise that TLR7/8 DC vaccination strategies should be combined with hypomethylating agents or checkpoint inhibition to augment immune responses. Trial registration: The study was registered at https://clinicaltrials.gov on 17 October 2012 (NCT01734304) and at https://www.clinicaltrialsregister.eu (EudraCT‐Number 2010‐022446‐24) on 10 October 2013. Abstract : Dendritic cell (DC) vaccination is a promising strategy to induce anti‐leukaemic immune responses. In this first‐in‐human phase I trial, TLR7/8‐matured DCs transfected with RNA encoding two leukaemia‐associated antigens (WT1 and PRAME) and CMVpp65 were used as post‐remission therapy for AML patients at high risk of relapse. DC generation was feasible, and administration was safe and resulted in local inflammatory responses and expanded antigen‐specific CD8 + and CD4 + T cells in peripheral blood; clinical benefit correlated with younger age and immune responders.